Management engineering for effective healthcare delivery principles and applications - Kolker, Alexander, 1952-; Story, Pierce; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book illustrates the power of management engineering for quantitative managerial decision-making in healthcare settings, that assists in predicting performance and/or real resource requirements and allowing decision-makers to be truly proactive rather than reactive"--
Efficient managerial decision-making in healthcare settings : examples and fundamental principles -- Dynamic capacity management (DCAMM) in a hospital setting -- Simulation modeling of healthcare delivery -- Simulation applications in a healthcare setting -- Modeling clinical engineering activities to support healthcare technology management -- Intensive care unit operational modeling and analysis -- Human-centered systems engineering : managing stakeholder dissonance in healthcare delivery -- Enabling real-time management and visibility with RFID -- Healthcare delivery as a service system : barriers to co-production and implications of healthcare reform -- Using simulation to design and improve an outpatient procedure center -- Reducing consultation waiting time and overtime in outpatient clinic : challenges and solutions -- Reducing patient waiting time at an ambulatory surgical center -- Scheduling healthcare systems : theory and applications -- Appointment order outpatient scheduling system with consideration of ancillary services and overbooking policy to improve outpatient experience -- Electronic health record adoption, considerations, and future direction -- Electronic medical records (EMR) : issues and implementation perspectives.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed August 8, 2011).
Keywords: Health services administration -- Decision making; Medical care; Delivery of Health Care -- organization & administration; Decision Making; Health Services Administration; Leadership; Models, Organizational; Practice Management -- organization & administration; Dynamic capacity management; EHR and EMR; Healthcare management engineering; Intensive care unit operational modeling; Outlier management; Patient flow; Probabilistic resource optimization; Radio frequency identification; Simulation modeling; Stakeholder dissonance; Electronic books